Is catheter-tissue contact force value important for ablation of ventricular arrhythmias originating from the left ventricular papillary muscles? - Baran, Jakub; Skrzyńska-Kowalczyk, Martyna; Piotrowski, Roman; Sikorska, Agnieszka; Kryński, Tomasz; Kułakowski, Piotr (Frontiers in Cardiovascular Medicine, 2023)
Background Good catheter-tissue contact is mandatory to create effective ablation lesions. The minimal contact force value for ablation of arrhythmias originating from the left ventricle is 8.0–10.0 grams but is not known for arrhythmias arising from papillary muscles. Purpose To analyze contact force values during successful ablation procedures of arrhythmias originating from the left ventricular papillary muscles. Methods 24 consecutive patients (mean age 57.9 ± 11.9 years, 16 males) underwent ablation of premature ventricular complexes originating from left ventricular papillary muscles with the use of CARTO electro-anatomical system and intracardiac echocardiography. Results Acute complete abolition of ventricular ectopy was obtained in 23 (96%) patients. The fluoroscopy time was 3.9 ± 3.5 min and procedure duration - 114.8 ± 37.9 min. The mean contact force during successful ablations was 3.0 ± 1.1 grams and 3.18 ± 1.8 grams for antero-lateral and postero-medial papillary muscle, respectively (NS). The mean contact force during a single unsuccessful ablation was 3.0 grams. At control Holter ECG, the mean Ectopy Burden was Reduced in the Antero-Lateral Papillary Muscle Group from 18.0% ± 7.9% to 2.6% ± 2.9% (p = 0.005415) and in the Postero-Medial Papillary Muscle Group - from 34.8% ± 13.7%–1.7% ± 1.3% (p = 0.012694). During Median 27 (IQR: 17–34) Months of Follow-up There one Recurrence of Arrhythmia. Conclusion The values of contact force for successful ablation of ventricular ectopy originating from the left ventricular papillary muscles may be much lower than those for ablation of other foci which questions the role of contact force measurement when ablating these arrhythmias.